MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING - RAHMI PRATIWI (Jurnal Edukasi dan Penelitian Matematika, 2021)
Mathematics learning has goals that must be achieved, one of which is the ability to solve mathematical problems. The poor ability of students to solve math problems is due to the suboptimal learning process. Therefore, in order to overcome this problem, a learning model that can improve student's mathematical problem-solving ability is needed, one of which is a problem-based learning model. The purpose of this research is to theoretically describe whether the problem-based learning model can improve student's mathematical problem-solving ability. This type of research is literature research, which aims to improve mathematical problem-solving capabilities through problem-based learning models. The conclusion of this research is to apply a problem-based learning model that has a tendency to improve student’s mathematical problem-solving abilities. The articles on the indicators of these abilities describe these abilities related to stages in the Problem Based Learning model. Keywords__mathematical problem solving abilities, Problem Based Learning